The maze runner series - Dashner, James (Chicken House, 2013)
The pulse-pounding multimillion-selling adventure series - now a major motion picture. When the lift cranks open, the only thing Thomas remembers is his first name. But he's not alone - an army of boys welcomes him to the Glade, an encampment at the centre of a terrible maze. The Gladers have no idea why they're there, or what's happened to the world outside. But following the arrival of a girl with a message, they must find a way out - or die. Titles in this collection:? The Maze Runner? The Scorch Trials? The Death Cure? The Kill Order? The Fever Code.